Woman to woman: an everywoman's guide to lesbian sexuality - Booth, Carol (Simon & Schuster, 2002)
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

Queer globalizations: citizenship and the afterlife of colonialism - Cruz, Arnaldo; Manalansan, Martin F. (Sexual cultures, 2002)
Globalization has a taste for queer cultures. Whether in advertising, film, performance art, the internet, or in the political discourses of human rights in emerging democracies, queerness sells and the transnational circulation of peoples, identities and social movements that we call "globalization" can be liberating to the extent that it incorporates queer lives and cultures. From this perspective, globalization is seen as allowing the emergence of queer identities and cultures on a global scale. The essays in Queer Globalizations bring together scholars of postcolonial and lesbian and gay studies in order to examine from multiple perspectives the narratives that have sought to define globalization. In examining the tales that have been spun about globalization, these scholars have tried not only to assess the validity of the claims made for globalization, they have also attempted to identify the tactics and rhetorical strategies through which these claims and through which global circulation are constructed and operate.
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; racisme; régions géographiques; sexualité; shm4000; système colonial; systèmes d'oppressions; thématiques; états-unis

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

Femmes et sexualité(s) - Institut de recherches et d'études féministes (FéminÉtudes, 2002)
Cette publication de 2002 aborde les enjeux des femmes et des sexualité(s) *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; féminétudes; identités LGBTQIA2+; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; sexualité; sexualité des femmes*; thématiques; travail; travail du sexe

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

A butch among the belles - Strickland, Bonnie R. (Journal of Lesbian Studies, 2002)
This memoir of a 65-year-old “butch” lesbian describes her growing-up days in the South and her subsequent professional identity as a university professor and psychologist. The article includes feelings about being raised as a girl while feeling male. Personal reactions to family pressures to conform to a rigid sex role are noted and some attention is given to the effects of living an adult life in the closet.
Keywords: amériques; butch; identités LGBTQIA2+; personnes lesbiennes; ressource en ligne; régions géographiques; sexualité; thématiques; états-unis